2010
DOI: 10.1016/j.jvs.2010.08.072
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Gastrocnemius and Soleal Vein Thrombosis: Should These Patients Receive Therapeutic Anticoagulation?

Abstract: Compared with patients who underwent ligation, patients receiving TIVS had fewer amputations (47% vs 0%) and fewer fasciotomy procedures (93% vs 43%; P Ͻ .05). Mortality was 72% in the ligation group vs 43% in the TIVS group. In the patients treated with a TIVS, no TIVS thrombosed, and the mean shunt time was 22.3 hours.Comment: Temporary intravascular shunts have long been used as a method of temporarily restoring arterial circulation in patients with peripheral arterial injuries distal to the axillary crease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 0 publications
3
36
0
Order By: Relevance
“…28) Another study reported that the incidence of associated VTE related to isolated calf muscular DVTs is dramatically reduced with therapeutic anticoagulation. 29) Our results emphasize the clinical importance of calf DVTs, especially those in the soleal vein and its drainage veins, from the viewpoint of lethal PE prophylaxis.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…28) Another study reported that the incidence of associated VTE related to isolated calf muscular DVTs is dramatically reduced with therapeutic anticoagulation. 29) Our results emphasize the clinical importance of calf DVTs, especially those in the soleal vein and its drainage veins, from the viewpoint of lethal PE prophylaxis.…”
Section: Discussionsupporting
confidence: 66%
“…11,27) Previous investigations have indicated that isolated calf DVTs have better prognosis, with a relatively lower incidence of complications of proximal propagation (3%-32% of cases 10,[13][14][15]24,27,28,29) ) and PE (2%-21% of cases 10,11,[13][14][15]30) ). However, an epidemiological study revealed that the prognosis of patients with bilateral distal DVT is as poor as that of patients with bilateral proximal DVT in terms of mortality and the recurrence rate of DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have signaled that these thromboses have a risk of extension to proximal veins. 2,48 Schwarz et al in 2 subsequent studies reported different results. In the first study, 49 they found few complications in patients receiving therapeutic doses of LMWH for 10 days plus compression therapy vs those receiving compression alone.…”
Section: What Is Done In Studies and In Clinical Practicementioning
confidence: 96%
“…It is believed that fluctuations in soleal vein thrombosis are repeated recurrences due to sustained risk factors and can present proximal development or an embolic source. [31][32][33][34] DOACs are innovative drugs that circumvent complex patient management issues, such as frequent blood sampling, diet restriction, or drug interactions, which were problems in the warfarin-only era. 6 Four DOACs are clinically available for the prevention of VTE after orthopedic surgery.…”
Section: Effects Of Edoxaban On the Incidence Of Vtementioning
confidence: 99%